2013
DOI: 10.1097/opx.0b013e3182924017
|View full text |Cite
|
Sign up to set email alerts
|

3-D Choroidal Thickness Maps from EDI-OCT in Highly Myopic Eyes

Abstract: Three-dimensional choroidal thickness maps obtained via EDI-OCT are useful for quantifying choroid thickness in subjects with high myopia more accurately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
15
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 26 publications
7
15
1
Order By: Relevance
“…Regarding choroidal thickness, the present findings are in agreement with previous reports describing a thinner choroid in high myopia than in healthy eyes, both subfoveally and in different peripheral locations 2,20,29,30,37 . Besides, whereas in the control group the thickest choroid was found subfoveally, in the myopic group this area was the thinnest.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding choroidal thickness, the present findings are in agreement with previous reports describing a thinner choroid in high myopia than in healthy eyes, both subfoveally and in different peripheral locations 2,20,29,30,37 . Besides, whereas in the control group the thickest choroid was found subfoveally, in the myopic group this area was the thinnest.…”
Section: Discussionsupporting
confidence: 93%
“…The observation that foveal RT (measured at the trough of the foveal pit) tends to increase with increasing myopia in our study (although not significantly so), is consistent with previous reports, 18, 37, 38 and is particularly interesting, given that the latter studies also described thinning of the peripheral retina in myopic eyes. Together these data suggest that the central retina is somehow protected against the stretching forces accompanying increased globe expansion, and assumed to underlie the peripheral retinal thinning in myopic eyes.…”
Section: Discussionsupporting
confidence: 94%
“…15, 16 The choroid, a dense vascular structure underlying the retina, plays an important role in meeting the high nutrient and energy demands of the outer retina, with the central avascular foveal region being dependent on the choroid exclusively. In high myopia, the choroid is frequently structurally compromised, with both choroidal neovascularization 16, 17 and chorioretinal atrophy 18 being reported. Previous studies have also shown correlations between axial length and some other ocular parameters, apart from central refractive error, for example, peripapillary retinal nerve fiber layer thickness.…”
mentioning
confidence: 99%
“…Thicker choroidal measurements have been found in central serous chorioretinopathy, Vogt-Koyanagi-Harada disease, multiple evanescent white dot syndrome, adult onset foveomacular vitelliform dystrophy, and macular telangiectasis type 2. 913 Thinner choroid thickness measurements have been observed inferior to the optic nerve, 14 in highly myopic eyes, 15 in diabetic eyes, 16,17 and in eyes with reticular pseudodrusen (RPD), also known as subretinal drusenoid deposits (SDDs). 1821 In age-related macular degeneration, it is the presence of RPD that has been associated with subfoveal and peripapillary choroidal thinning rather than the diagnosis of AMD.…”
mentioning
confidence: 99%